Sex in Cetaceans Morphology, Behavior, and the Evolution of Sexual Strategies - Würsig, Bernd; Orbach, Dara N. (Springer International Publishing : Imprint: Springer, 2023)
Sex in Cetaceans provides an up-to-date review of multi-faceted aspects related to mating and reproduction in toothed and baleen whales. This open access book begins with discussions of sexual selection and anatomical traits related to mating and diversity between the sexes. The functions of non-conceptive copulations are reviewed as are different research techniques applied to explore sex in cetaceans. Authors and editors build knowledge of female and male social, mating, and parental strategies and tactics for several specific toothed dolphin/porpoise/whale species and baleen whale species. It concludes with a discussion of potential conservation efforts and ways to help especially beleaguered species and populations the world over. The volume is intended as a major primer of cetacean sex for undergraduate and graduate students, new and established researchers in the field, and the public wishing to learn more.